Which Nonsurgical Treatments Do Patients Believe Are Most Effective for Hip and Knee Arthritis?. (May 2020) - Nahhas, Cindy R.; Fuller, Brian C.; Hannon, Charles P.; Gerlinger, Tad L.; Nam, Denis; Della Valle, Craig J.
Abstract : Background: The purpose of this study was to determine which nonsurgical treatments patients believe are most effective for managing pain secondary to hip and knee arthritis. Methods: Five hundred sixty-five consecutive patients were administered an anonymous questionnaire developed in consultation with a center with expertise in survey design. Statistical analyses included Student t -test, Fisher Exact, Wilcoxon Rank-Sum test, and generalized cost-effectiveness analysis. Results: Four hundred thirty-six patients completed the questionnaire (response rate 77.2%). Opioids (52 of 118; 44.1%), prescription nonsteroidal anti-inflammatory drugs (NSAIDs) (67 of 200; 33.5%), and corticosteroid injections (87 of 260; 33.5%) were reported as most effective. Stem cell and platelet-rich plasma injections were selected by three of 12 (25.0%) and three of 15 patients (19.5%), respectively, and physical therapy (PT) by 50 of 257 patients (19.5%). Twenty-five percent of respondents received opioids, commonly prescribed by primary care providers (48.2%) and orthopaedic surgeons (39.5%). Opioid use correlated with lower patient-reported effectiveness of PT, NSAIDs, and corticosteroid injections ( P < 0.05). The highest cost-effectiveness ratios were NSAIDs, opioids, and acetaminophen (2.2, 3.7, 4.0, and 5.4, respectively). The lowest cost-effectiveness ratios were stem cell injections, platelet-rich plasma injections, and PT (1966.7, 520.8, and 138.6, respectively). Conclusions: The nonsurgical treatments that are reported by patients to be most effective are oftentimes the least expensive.